Changes in hunger and fullness in relation to gut peptides before and after 8 weeks of alternate day fasting. Issue 6 (December 2016) - Hoddy, Kristin K.; Gibbons, Catherine; Kroeger, Cynthia M.; Trepanowski, John F.; Barnosky, Adrienne; Bhutani, Surabhi; Gabel, Kelsey; Finlayson, Graham; Varady, Krista A.
Summary: Background & aims: Alternate day fasting (ADF; 25% energy intake "fast day", alternated with an ad libitum intake "feed day") is effective for weight loss. Whether or not ADF modulates hunger, fullness and gut peptides in a way that enhances dietary compliance and weight loss, remains unknown. Accordingly, this study examined the effect of ADF on postprandial appetite ratings and gut peptides. Methods: Obese subjects (n = 59) participated in an 8-week ADF protocol where food was provided on the fast day. Results: Body weight decreased (P < 0.0001) by 3.9 ± 0.6 kg after 8 weeks of diet. Reductions (P < 0.05) in fat mass (−2.2 ± 0.2 kg), fat free mass (−1.4 ± 0.2 kg), visceral fat mass (−0.1 ± 0.1 kg), and resting metabolic rate (RMR; −104 ± 28 kcal/day) were also observed. Fasting leptin and insulin decreased (P < 0.05), while AUC ghrelin levels increased (P < 0.05). Despite these metabolic changes, there was no increase in subjective hunger by the end of the study. Furthermore, fullness and PYY increased (P < 0.05). Fat free mass and RMR were not related to hunger or ghrelin at any time point. Conclusion: These findings suggest that the absence of a compensatory increase in hunger in conjunction with an increase in sensations of fullness may contribute to the weight loss efficacy of an 8-week ADF regimen.